2015
DOI: 10.1002/etc.3077
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and selenium accumulation in the Colorado River food web, Grand Canyon, USA

Abstract: Mercury (Hg) and selenium (Se) biomagnify in aquatic food webs and are toxic to fish and wildlife. The authors measured Hg and Se in organic matter, invertebrates, and fishes in the Colorado River food web at sites spanning 387 river km downstream of Glen Canyon Dam (AZ, USA). Concentrations were relatively high among sites compared with other large rivers (mean wet wt for 6 fishes was 0.17-1.59 μg g(-1) Hg and 1.35-2.65 μg g(-1) Se), but consistent longitudinal patterns in Hg or Se concentrations relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Accumulations of selenium and mercury individually can result in irreversible injury during early development of fish (Mailman et al 2014; Walters et al 2015). Some researchers have reported evidence of selenium moderating the negative effects of mercury in freshwater fish when accumulated together (Peterson et al 2009), but underlying mechanisms and the amount of excess selenium needed are unclear (Khan and Wang 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulations of selenium and mercury individually can result in irreversible injury during early development of fish (Mailman et al 2014; Walters et al 2015). Some researchers have reported evidence of selenium moderating the negative effects of mercury in freshwater fish when accumulated together (Peterson et al 2009), but underlying mechanisms and the amount of excess selenium needed are unclear (Khan and Wang 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Walters et al (2015) found high mercury and selenium concentrations in fish food webs from the Colorado River in the Grand Canyon. Mercury contamination has been found in several fish species in the upper Colorado River basin.…”
mentioning
confidence: 99%
“…Including non-essential trace elements is also crucial to a holistic stoichiometric approach (MacNeill et al, 2016). Arsenic (As), mercury (Hg), selenium (Se) and other non-essential trace elements have been well studied individually (Boening, 2000; Farag et al, 2003; Schaller et al, 2010; Walters et al, 2015), but their pairings with other, more common elements have less frequently been evaluated (but see Wang et al, 2013). Integrating trace elements, their interactions with each other and their interactions with C, N, and P into studies of ES will provide a more complete picture of elemental cycling in ecosystems (Wang et al, 2013).…”
Section: Empirical Assessmentsmentioning
confidence: 99%
“…The potential of MeHg to be biomagnified presents a health hazard to aquatic organisms and terrestrial wildlife with trophic linkages to aquatic food webs (e.g., those that consume emergent aquatic insects; [22][23][24]). While many studies have examined the movement of contaminants between habitats (e.g., Du et al [25]), few studies have concurrently measured the fluxes of contaminants and fatty acids from streams to riparian zones; even though stream contamination is widespread [26].…”
Section: Introductionmentioning
confidence: 99%